2007
DOI: 10.1113/expphysiol.2006.033787
|View full text |Cite
|
Sign up to set email alerts
|

Sleep and the metabolic syndrome

Abstract: The metabolic syndrome represents a clustering of several interrelated risk factors of metabolic origin that are thought to increase cardiovascular risk. It is still uncertain whether this clustering results from multiple underlying risk factors or whether it has a single cause. One metabolic abnormality that may underlie several clinical characteristics of the metabolic syndrome is insulin resistance. This review discusses the evidence that sleep disturbances (obstructive sleep apnoea, sleep deprivation and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
104
1
7

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3
3

Relationship

1
9

Authors

Journals

citations
Cited by 152 publications
(114 citation statements)
references
References 134 publications
0
104
1
7
Order By: Relevance
“…114 Finally, related metabolic dysregulation such as leptin resistance and the metabolic syndrome also have been linked to OSA. 51,115 Thrombosis OSA also been associated with increased platelet activation, increased fibrinogen, and other potential markers of thrombotic risk. 116 However, additional studies are needed to more definitively evaluate the role of hemostatic mechanisms and to confirm any hypercoagulable state in OSA.…”
Section: Endothelial Dysfunctionmentioning
confidence: 99%
“…114 Finally, related metabolic dysregulation such as leptin resistance and the metabolic syndrome also have been linked to OSA. 51,115 Thrombosis OSA also been associated with increased platelet activation, increased fibrinogen, and other potential markers of thrombotic risk. 116 However, additional studies are needed to more definitively evaluate the role of hemostatic mechanisms and to confirm any hypercoagulable state in OSA.…”
Section: Endothelial Dysfunctionmentioning
confidence: 99%
“…The mechanism could be related to increased abdominal visceral obesity altering chest wall and upper airway mechanics and reducing functional residual capacity making subjects more vulnerable to hypoxemia during sleep [24]. It has also been shown that SDB can independently induce MetS by decreasing insulin sensitivity in both animals and humans [25]. A recent study by Tasali et al in women with PCOS and SDB showed the reversal of key determinants of the MetS after 8-weeks of CPAP treatment including significant improvements in: insulin sensitivity, daytime diastolic blood pressure, heart rate variability, and daytime sleepiness [26].…”
Section: Discussionmentioning
confidence: 99%
“…A link between prolonged sleep disturbance and the increasing worldwide prevalence of the metabolic syndrome has been proposed [15,17,32]. For instance, it has been reported that clock gene expression is impaired in individuals with metabolic syndrome, and, further, that impairments in transcript levels of PER3 in human leukocytes occur in diabetic subjects and gestational diabetic women [33,34].…”
Section: Discussionmentioning
confidence: 99%